2023
DOI: 10.1186/s13027-023-00514-x
|View full text |Cite
|
Sign up to set email alerts
|

p16INK4a and pRb expression in laryngeal squamous cell carcinoma with and without infection by EBV or different genotypes of HPV: a retrospective study

Jose Manuel Vazquez-Guillen,
Gerardo C. Palacios-Saucedo,
Alondra Yamileth Alanis-Valdez
et al.

Abstract: Background Laryngeal squamous cell carcinoma (LSCC) represents one of the principal tumors of the head and neck. Human papillomavirus (HPV) and Epstein–Barr virus (EBV) are considered risk factors for the development and the clinical prognosis of LSCC. High levels of p16INK4a are suggested as a surrogate marker of HPV or EBV infection in some head and neck tumors but in LSCC is still controversial. Furthermore, pRb expression may be considered an additional biomarker but it has not been clearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…The role of EBV in LSCC is controversial, as difficulties have been reported in detecting its presence in this type of cancer or it has shown a low prevalence [ 33 ]. However, both EBV and HPV are viruses capable of producing oncoproteins that can promote carcinogenesis and tumor progression [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of EBV in LSCC is controversial, as difficulties have been reported in detecting its presence in this type of cancer or it has shown a low prevalence [ 33 ]. However, both EBV and HPV are viruses capable of producing oncoproteins that can promote carcinogenesis and tumor progression [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…HPV is detected in a subset of HNCs outside of the oropharynx (larynx, oral cavity, hypopharynx, nasopharynx); however, the prevalence is much lower than in the oropharynx and the clinical significance is unclear [42]. While the prevalence of HPV positivity has been increasing in laryngeal and oral cavity cancer, there does not seem to be an association between HPV status and survival [43,44]. At this time, testing for HPV in non-oropharynx HNCs is not currently recommended [45].…”
Section: Hpv Tumor Status In Non-oropharynx Hnc Sitesmentioning
confidence: 99%
“…Many studies have confirmed that HPV mainly combines with the tumor suppressors p53 and pRB through the E6 and E7 proteins to cause uncontrolled cell proliferation, resulting in damage or even loss of cellular DNA self-repair function, leading to cancer. 7 , 8 , 9 , 10 The characteristic of HPV E6 protein is that it has two structural domains, which contain zinc finger structures, and these zinc finger structures bind to DNA and RNA and mediate protein-protein interactions to realize the cell transformation of E6 protein. 11 The E6 protein mainly causes mutations in the tumor suppressor gene p53 and binds to the p53 protein, leading to its inactivation and degradation of the p53 protein, thereby causing malignant expansion of cells.…”
Section: Introductionmentioning
confidence: 99%